Siraitia grosvenorii Extract Protects Lipopolysaccharide-Induced Intestinal Inflammation in Mice via Promoting M2 Macrophage Polarization - Huining Wu; Mengru Guo; Linlu Zhao; Jin Zhang; Jieyi He; Anning Xu; Zhichao Yu; Xingbin Ma; Yanhong Yong; Youquan Li; Xianghong Ju; Xiaoxi Liu (MDPI AG, 2024)
Siraitia grosvenorii has anti-inflammatory, antioxidant, and immune-regulating effects, while macrophages play an important role in reducing inflammation. However, it is still unclear whether Siraitia grosvenorii extract (SGE) is effective in reducing inflammation by regulating macrophages. This study investigated the regulatory effect of SGE on macrophage polarization in a lipopolysaccharide (LPS)-induced intestinal inflammation model after establishing the model in vitro and in vivo. The results from the in vivo model showed that, compared with the LPS group, SGE significantly improved ileal morphology, restored the ileal mucosal barrier, and reduced intestinal and systemic inflammation by increasing CD206 and reducing iNOS proteins. In the in vitro model, compared with the LPS group, SGE significantly reduced the expression of iNOS protein and cytokines (TNF-α, IL-1β, and IFN-γ) while significantly increasing the protein expression of CD206 in RAW264.7 cells. In conclusion, SGE can alleviate intestinal inflammation, protect the mucus barrier, and block the systemic immunosuppressive response by increasing M2 macrophages.